2020
DOI: 10.1590/s1678-3921.pab2020.v55.01643
|View full text |Cite
|
Sign up to set email alerts
|

Development of SNP markers for grain yield screening of Brazilian rice cultivars

Abstract: The objective of this work was to identify and validate single-nucleotide polymorphism (SNP) markers related to grain yield in rice (Oryza sativa) core collection. The genome-wide association studies (GWAS) methodology was applied for genotyping of 541 rice accessions by 167,470 SNPs. The grain yield of these accessions was estimated through the joint analysis of nine field experiments carried out in six Brazilian states. Fifteen SNPs were significantly associated with grain yield, and out of the ten SNPs conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…GWAS was used for genotyping of 541 rice accessions by 167470 SNPs. The study concluded 15 SNPs to be significantly related to grain yield (Pantalião et al, 2020). Additionally, trait-linked simple sequence repeat (SSR) markers were deployed to study an important rice agronomic trait-aroma (Jasim Aljumaili et al, 2018).…”
Section: Genomics and Transcriptomics In Rice Trait Improvementmentioning
confidence: 99%
“…GWAS was used for genotyping of 541 rice accessions by 167470 SNPs. The study concluded 15 SNPs to be significantly related to grain yield (Pantalião et al, 2020). Additionally, trait-linked simple sequence repeat (SSR) markers were deployed to study an important rice agronomic trait-aroma (Jasim Aljumaili et al, 2018).…”
Section: Genomics and Transcriptomics In Rice Trait Improvementmentioning
confidence: 99%